Effects of Language Barrier on Academic Performance of First Year Undergraduate Medical Students in Jamnagar (GAIMS Journal of Medical Sciences, 2025)
Background: Language proficiency plays a foundational role in the success of medical students, especially in multilingual countries like India, where students often come from diverse linguistic backgrounds. The transition from vernacular language-based schooling to English-medium medical education creates a significant challenge for first-year MBBS students. These students often struggle with understanding medical terminology, lectures and textbooks, all of which are primarily in English. This language barrier can impede their academic performance, communication skills and confidence, which are critical to becoming competent healthcare professionals.Objectives: This study aimed to assess the extent to which language barriers affect the academic performance of first-year MBBS students.Materials and Methods: This is an institution based cross-sectional study. Total 220 students participated in the study. A preformed questionnaire was given to the students. Result was obtained by the answers given by the students.Results: A total of 220 participants responded to the survey, including 118 (53.6%) males and 102 (46.4%) females. 160 (72.7%) of the total participants had studied in Gujarati medium, 16 (7.3%) of the total participants had studied in Hindi medium, while 44 (20%) of the total participants had studied in English medium. The majority 140 (63.7%) of the participants stated that they frequently used dictionaries for their studies and 80 (36.3%) did not use dictionaries. The results indicated that most participants, more specifically 110 (50%) medical students were neither comfortable nor uncomfortable (Neutral) with the English language, followed by 74 (33.6%) who were comfortable as opposed to 36 (16.4%) who were very uncomfortable.Conclusion: English Language Proficiency Program (ELPP) can be used at a level of medical colleges to increase the interest and academic performance of the students.